PENGARUH PERSEPSI KONTEN ONLINE DESTINASI WISATA TERHADAP INTERAKSI PEMASARAN DIGITAL DAN KEPUTUSAN PEMBELIAN - Kakanita Ari Puspitasari; Asep Rokhyadi Permana Saputra (Universitas Sarjanawiyata Tamansiswa, 2025)
This research is quantitative. It has several objectives, including examining the effect of online information quality on digital marketing interactions, user-friendly accessibility on digital marketing interactions, digital marketing interactions on purchasing decisions, online information quality on purchasing decisions, and user-friendly accessibility on purchasing decisions. All questionnaire items used in this study were valid and reliable. All classical assumption tests, including normality, heteroscedasticity, and multicollinearity, were found to have passed and were suitable for use. For data analysis, the researcher used multiple linear regression analysis using IBM SPSS Statistics 26 software. The study involved 60 respondents. The results showed that online information quality had no significant effect on digital marketing interactions, user-friendly accessibility had a significant effect on digital marketing interactions, digital marketing interactions had no significant effect on purchasing decisions, online information quality had a significant effect on purchasing decisions, and user-friendly accessibility had no significant effect on purchasing decisions.